Non-orthogonal multiple access: basic interference management technique - Khan, Rabia; Nalin K. Jayakod, Dushantha; Chen, Bin (International Journal of Engineering and Technology, 2018)
Non Orthogonal Multiple Access (NOMA) is a technique that offers spectral efficiency, Quality of Service (QoS), user fairness, low latency, high data rate, and overall better performance as compared to Orthogonal Multiple Access (OMA). The main feature of NOMA is the efficient utilization of spectrum due to increasing demand of data rate. We have introduced a new technique known as MNOMA (Modulation based NOMA) which will help in reducing the interference and complexity of signals decoding, not only in uplink but downlink as well. We have achieved the target of proposed technique by working on superposition coding (SC) of the system. In NOMA interference between users is certain due to removal of orthogonality in spectrum. The problem of interference has been tackled with superposition coding and a number of SICâ€™s (Successive Interference Cancellation) performed on the receiver's end. With MNOMA technique we have tried to reduce the complexity of system by integrating the basic orthogonality in the transmitter instead of spectrum. In this paper, we have shown the reduced expression of data rate for the proposed technique, which shows reduced complexity of the system in terms of SIC, Symbol Error Rate (SER), and better data rate of the proposed technique as compare to conventional OMA.Â Â